Dimethyl fumarate eliminates differentially culturable Mycobacterium tuberculosis in an intranasal murine model of tuberculosis - Glenn, Sarah M.; Turapov, Obolbek; Makarov, Vadim; Kell, Douglas B.; Mukamolova, Galina V. (Frontiers in Cellular and Infection Microbiology, 2022)
Tuberculosis (TB) claims nearly 1.5 million lives annually. Current TB treatment requires a combination of several drugs administered for at least 6 months. Mycobacterium tuberculosis (Mtb), the causative agent of TB, can persist in infected humans and animals for decades. Moreover, during infection, Mtb produces differentially culturable bacteria (DCB) that do not grow in standard media but can be resuscitated in liquid media supplemented with sterile Mtb culture filtrates or recombinant resuscitation-promoting factors (Rpfs). Here, we demonstrate that, in an intranasal murine model of TB, Mtb DCB are detectable in the lungs after 4 weeks of infection, and their loads remain largely unchanged during a further 8 weeks. Treatment of the infected mice with dimethyl fumarate (DMF), a known drug with immunomodulatory properties, for 8 weeks eliminates Mtb DCB from the lungs and spleens. Standard TB treatment consisting of rifampicin, isoniazid, and pyrazinamide for 8 weeks reduces Mtb loads by nearly four orders of magnitude but does not eradicate DCB. Nevertheless, no DCB can be detected in the lungs and spleens after 8 weeks of treatment with DMF, rifampicin, isoniazid, and pyrazinamide. Our data suggest that addition of approved anti-inflammatory drugs to standard treatment regimens may improve TB treatment and reduce treatment duration.